Stimulasi Perkembangan Fisik Motorik Anak Autisme Melalui Terapi Perilaku Okupasi di TK Adni Surabaya - Mei Ariani Kusumawati; Pamuji Pamuji (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research discusses the effect of providing occupational therapy on fine motor development in autistic children at ADNI Kindergarten in Surabaya. The aim of the research is to see the effect of providing occupational therapy on the development of fine motor skills in autistic children at ADNI Surabaya Kindergarten. Occupational therapy is a therapy used for autistic children and can also be applied to children/adults who experience autism, speech delays, developmental disorders and other growth and development delays. Occupational Therapy aims to help children who experience problems with their fine motor skills. This therapy can be used as an option to try to improve children's physical and mental abilities to take part in activities that involve children's gross and fine motor skills so that children can be independent and can develop and be accepted in society. This research will be carried out at the ADNI Surabaya Kindergarten. The methodology used is a quantitative method with a Pre-Experimental design. Based on the results of the analysis, the change in the mean concentration value before and after being influenced by Occupation showed that the Pre-test value was mean = 1.38 and the Post-test value experienced a change, namely mean = 1.50. Meanwhile, the statistical test results obtained a p value of 0.024, which means that there is an influence of Occupational Therapy on the development of Fine Motor in Autistic children at ADNI Surabaya Kindergarten in 2024.